Sustainability Indicators of the Banana and Lemongrass Intercropping System in Different Harvest Seasons: Growth, Yield, Seasonality and Essential Oil Properties - Jesus, Paulo Ricardo Rodrigues de [UNESP]; Leonel, Sarita [UNESP]; Silva, Marcelo de Souza [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Leonel, Magali [UNESP]; Cândido, Hebert Teixeira [UNESP]; Tecchio, Marco Antonio [UNESP]; Molha, Nicholas Zanette [UNESP]; Domiciano, Vinicius Martins [UNESP] (MDPI, 2025)
Lemongrass (Cymbopogon citratus) has potential for intercropping with banana (Musa spp.) plants, thus contributing to the sustainability of plantations. The study evaluated the growth and yield of ‘Prata Anã’ banana and seasonality, yield and essential oil properties of lemongrass grown in intercropping and the land equivalent ratio. A randomized block design in a split plot arrangement was used, evaluating two cropping systems (sole crop and intercropping) and three harvest seasons during the year for lemongrass and two harvest seasons for banana, separately. The banana can be intercropped with lemongrass without interfering with its growth and production. The biomass production and essential oil yield of lemongrass differed according to cropping system and seasonality. The chemical composition of the essential oil showed stability in the concentration of citral (mixture of neral and geranial), with an average of 94.43%. Seasonal variations were observed in the content of these compounds and other components of the essential oil, emphasizing the importance of the time of harvest in the overall value of the oil. The result demonstrates the viability of intercropping, which not only provides crop yields for both species and produces more per unit area than a sole crop but also optimizes the use of resources and promotes more sustainable farming practices.
Keywords: consortium; Cymbopogon citratus; geranial; land equivalent ratio; Musaspp; neral; sole crop